Pengaruh Komposisi Pasir Cetak Terhadap Mutu Cetakan Pasir Coran Aluminium - Bukhari Bukhari; Nofriadi Nofriadi; Yanziwar Yanziwar (Politeknik Negeri Padang, 2019)
Casting is a manufacturing procces that use mold and molten metal to make parts. Geometry of the mold is almost same with the product. Shape of sand mold is negative shape of product that according to desire pattern. Making procces of mold must following right composition of sand mold. After through some test, strength of sand mold is depand on composition of mater. Value of the test on table 1 (89% sand, 9% water glass, and 2% water, has tensile strength 0,66 N/mm2 ) and compared to table 3. (85% sand, 9% water glass dan 2% water, has tensile strength 0,415 N/mm2 ). Based on the test, mold with 100% new sand has better collapse is mold with composition 94% new sand, 4% water glass, 2% water, has tensile strength 0,417 N/mm2, but, muld with 50% new sand 50% recycle sand has better collapse is mold with composition 45% new sand, 45% recycle sand, 6% water glass, and 4% water, has tensile strength 0,474 N/mm2.